Building a medical vocabulary - Leonard, Peggy C (W. B. Saunders, 1993)
The book presents a logical, step-by-step method for learning medical terminology. It includes new anatomic, diagnostic, and surgical terms. Exercises at the end of lessons gives a chance to identify word parts and combine them to form the terms encoutered in daily practice. It also presents a variety of crossword puzzles, multiple-choice questions, fill-in-the-blank questions, labeling exercises, case studies, and word pronunciation